2006
DOI: 10.1002/chir.20357
|View full text |Cite
|
Sign up to set email alerts
|

Solving multicomponent chiral separation challenges using a new SFC tandem column screening tool

Abstract: A tool for improved tandem column chiral supercritical fluid chromatography (SFC) method development screening was prepared by modification of a commercial analytical SFC instrument with two different software-controllable, six position high-pressure column selection valves, each controlling a bank of five different columns and a pass through line. The resulting instrument, which has the ability to screen 10 different individual columns and 25 different tandem column arrangements, is a useful tool for facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 14 publications
(13 reference statements)
0
41
0
1
Order By: Relevance
“…First, a wider range of CSPs will be tested, but derivatization of targeted molecule and column coupling can also be envisaged. Recently the SFC coupling of two different chiral columns in series has been reported for the resolution of the four stereoisomers of pharmaceutical compounds containing two chiral centers [168,169].…”
Section: The Domination Of the Polysaccharide Chiral Stationary Phasesmentioning
confidence: 99%
“…First, a wider range of CSPs will be tested, but derivatization of targeted molecule and column coupling can also be envisaged. Recently the SFC coupling of two different chiral columns in series has been reported for the resolution of the four stereoisomers of pharmaceutical compounds containing two chiral centers [168,169].…”
Section: The Domination Of the Polysaccharide Chiral Stationary Phasesmentioning
confidence: 99%
“…[49]. Two arrays of five chiral columns are used to screen chiral molecules using a standard gradient method (4% MeOH during 4 min, the ramp at 2%/min to 40% MeOH and hold for 3 min, 200 bar, 358C, 1.5 mL/ min, analysis time 25 min).…”
Section: Separations On Polysaccharide-based Cspmentioning
confidence: 99%
“…An effective screening system is the key for chiral method development. Welch et al (2007) reported a chiral SFC tandem column screening system. With modifi cation of a commercial analytical SFC instrument, two banks of fi ve different columns were individually controlled with two six -position high -pressure column selection valves.…”
Section: Sfc Chiral Separationsmentioning
confidence: 99%